2021
DOI: 10.32394/rpzh.2021.0152
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of dietary patterns and body composition parameters in the Polish population

Abstract: Background. Lifestyle factors are the key determinants of health. Diet exerts the great influence on the weight to height ratio and the body fat percentage. In addition to total energy intake, the type and quality of the diet can also play a role in the etiology of obesity in susceptible individuals. Objective. Aim of this study was to identify the dietary patterns of the Polish population and to determine the associations between these characteristics and body composition parameters. This study presents the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…From the group of volunteers, 16 healthy men were selected, who were characterized by a similar level of physical fitness described by the ACSM (The American College of Sports Medicine) as fair with VO 2 max 44.9-50.1 mL•kg −1 •min −1 [27]. The following inclusion criteria were applied: male sex, age between 20 and 30 years, and body composition parameters within the normal ranges for the Polish population [28,29]. The exclusion criteria included any contraindications to physical activity and contraindications to the use of vibration [18].…”
Section: Participantsmentioning
confidence: 99%
“…From the group of volunteers, 16 healthy men were selected, who were characterized by a similar level of physical fitness described by the ACSM (The American College of Sports Medicine) as fair with VO 2 max 44.9-50.1 mL•kg −1 •min −1 [27]. The following inclusion criteria were applied: male sex, age between 20 and 30 years, and body composition parameters within the normal ranges for the Polish population [28,29]. The exclusion criteria included any contraindications to physical activity and contraindications to the use of vibration [18].…”
Section: Participantsmentioning
confidence: 99%
“…On the other hand, the traditional Polish diet tends to be rich in meat, which could explain the higher protein intake among participating Polish pregnant women compared to Spanish participants [ 33 ]. In addition, potatoes, cabbage, and cereals are also very common foods in the Polish diet, which explains the higher intake of carbohydrates and fiber among participantsin Poland than among those in Spain in the present study [ 16 , 17 ]. These findings are consistent with other studies that have reported high protein and fiber intake in Eastern Europe [ 34 ].…”
Section: Discussionmentioning
confidence: 98%
“…Another example is the Polish diet, which is traditionally based on cereals, potatoes, vegetables, and meat. Although it is high in some nutrients that have been linked to certain health risks, such as saturated fat and sodium, the Polish diet also offers several benefits when consumed in moderation as part of a balanced diet, including being nutrient-dense, and high in protein and fiber [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%